The ball kicking speed: A new, efficient performance indicator in youth soccer - Rada, A.; Kuvacic, G.; De Giorgio, A.; Sellami, M.; Ardigò, L. P.; Bragazzi, N. L.; Padulo, J. (PLOS ONE, 2019)
Success in different soccer skills like kicking depends on motor abilities achieved. Kicking is a soccer fundamental, which depends on many different and complex factors (technique, foot-ball interaction, ball flight, etc.). Therefore, it is important to identify players that are able to perform faster kicks using both dominant and non-dominant leg. The current study investigated some basic variables of different soccer kicking speed and their relevance to success in youth soccer academy. 119 players from the first and the second division participated to this study. They were randomly divided into age groups (U-15, U-17, and U19) and team status (first team, reserves). The diagnostic ability of the different ball kicking speed tests in capturing differences between first team players and reserves among different age categories were computed using the receiver operating characteristics analysis. Results demonstrated that first team players achieved better results when comparing to reserves in each category. In addition, differences were greater in the U-15 and the U-17 than in the U-19 age group. In conclusion, ball kicking speed could be one of the possible identification tools to evaluate players' success in youth soccer.